When Did Social Experimentation Turn Into Social Science? The History of Randomised Controlled Trials and the Role of Science in Evidence-Based Policymaking - Neuwinger, Malte (Serendipities. Journal for the Sociology and History of the Social Sciences, 2026)
Supporters and critics of contemporary evidence-based policymaking (EBPM) widely view randomised controlled trials (RCTs) as an example of social science turned into an instrument of policymaking. Yet, historically, it is more adequate to say that policymaking turned RCTs into social science. Questioning standard views on the history of RCTs, this article argues that for most of the twentieth century, the scientific status of RCTs remained ambiguous—yet this did not stop them from gaining political credibility in social and medical applications. Until recently, experimental approaches were used not because they were regarded as the hallmark of science but because regulators and businesses felt that testing policies and drugs systematically was a sensible thing to do. Debates about the scientific status of RCTs became significant only in the 1980s when some leading social scientists opposed RCTs, viewing them as unscientific trial-and-error tinkering. RCTs eventually emerged as a generic instrument of evaluation in the 1990s, when they became regarded as politically credible and scientific. Judging from the history of its “gold standard”, present-day EBPM’s focus on social science instead of politics and business essentially reverses the direction in which it expects evidence to come to policy.